Занимательный русский язык: [5-11 кл.] (Н. М. Шанский) - Шанский Николай Максимович (1996)
Экземпляры: КХ (19971223) / Инвентарный номер: 1027669 / Цена: 9000.00 / Сис.шифр: 81.411.2-922 / Авт.знак: Ш 21 / ГРНТИ: 16 / ББК: 81.411.2-922